Socio economic programme (draft) by the Nava Sama Samja Partyfor a real development devoid of inflation & unemployment under a revolutionary left government. - Nava Sama Samja Party (NSSP) (Colombo : NSSP, 1992)
Bibliotheek François Vercammen
Engels
Brochure
Keywords: Sri Lanka